The effect of Hukou registration policy on rural-to-urban migrants' health - Marta Bengoa; Christopher Rick (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
Access to social services in China is connected to a system of household registration (Hukou system) determined by place of origin with difficult geographical transferability. As a consequence, a vast majority of rural-to-urban migrants do not have access to public health services in urban areas. This paper examines if restrictions on healthcare provisions - that are due to restrictions on migration and Hukou registration - are linked to poorer health for rural-to-urban migrants compared with non-migrant urban residents. We use data from two waves of the Longitudinal Survey on Rural Urban Migration in China that provide data on self-reported health and objectively measured health indicators - blood pressure and grip strength. Results indicate that even after accounting for migrant's characteristics that have known impacts on health, such as income, education, sex, marital status, and being underweight, the effect of the Hukou restriction policy is large, significantly negative, and acts as a key predictor of why rural-to-urban migrants' health deteriorates, especially during the early years since migration.
Keywords: C33; F22; I15; I18; J18; 330; internal migration; Hukou registration system; health outcomes; longitudinal data analysis